A Review of the Development and Role of Heterogeneous Catalysts for Biodiesel Production - Yuliana, Maria; Ismadji, Suryadi; Wijaya, Christian Julius; Soetaredjo, Felycia Edi; Gunarto, Chintya; Santoso, Shella Permatasari; Putro, Jindrayani Nyoo; Anggorowati, Adriana Anteng; Lourentius, Suratno (Widya Teknik, 2024)
Indonesian regulations regarding the implementation of B30 encourage a significant increase in biodiesel demand. Moreover, this implementation will continue to be increased to B35 in 2025 and is projected to reach B100 in 2045. This high demand for biodiesel needs to be supported by the development of adequate biodiesel production technology where the catalyst is one aspect that plays an important role in biodiesel production. The use of catalysts aims to accelerate biodiesel production so that high biodiesel yields and good quality are achieved. In biodiesel production, the choice of catalyst greatly influences the operating conditions, the products produced, the subsequent purification process, and the environmental impacts. Moreover, the changing trend in biodiesel raw materials from food to non-food ingredients requires the development of catalysts that are more suitable for the raw materials used in biodiesel production. The specific characteristics of each catalyst play an important role in the transesterification reaction to produce biodiesel where this needs to be supported and adapted to optimum operating conditions, especially in terms of alcohol-to-oil molar ratio, catalyst amount, temperature, pressure, and reaction time. This review provides a comprehensive overview of the various heterogeneous catalysts used to assist the transesterification reactions in biodiesel production.